Exú's Work – The Agency of Ritual Objects in Southeast Brazilian Umbanda - Eleonora A. Lundell (Journal of Ethnology and Folkloristics)
This article concentrates on the material side of religious intimacy in Afro-Brazilian Umbanda through an ‘ontographic’ perspective as well as looking at materiality as evidence. It is based on an eleven-month fieldwork among devotees, clients and individual practitioners of Umbanda in Southeast Brazilian metropolises, especially in São Paulo. In people’s experiences of spiritual work (trabalho) and spiritual development (desenvolvimento) carried out with Exús – guardians, guides and protectors who have, after their death, returned in order to work for people’s wellbeing – ritual objects (such as bodies, clothes, beverages, herbs, cigarettes, candles, songs) are seen as constitutive in knowledge production and life transformation. The central claim in this article is that diverse material and immaterial objects through which Exús interact and materialise, are not primarily symbolic nor representative, but are re-configurative.